Determinants of Taxable Enterprises Compliance In Bali, Indonesia - I Putu Artha Satria Wibawa; Ni Made Dwi Ratnadi; Maria M. Ratna Sari (PT Mattawang Mediatama Solution, 2024)
This study examines the determinants of compliance for taxable enterprises in Bali province. Taxable enterprises are parties appointed as collectors of value-added tax on the delivery of taxable goods and/or taxable services. Value-added tax is one type of tax that is more vulnerable to tax non-compliance. The three components of behavioural intention determinants based on the theory of planned behaviour developed into attitudes (tax morale and taxpayer awareness), subjective norms (tax justice and trust in government), and perceived behavioural control (tax authority power, tax convenience, and tax information) were tested to determine their influence on the compliance intention of taxable enterprises. The theory of slippery slope as a supporting theory explains that if trust in the tax authority is low and the power of the tax authority is weak, it can lead to taxpayer behaviour that tries to avoid taxes and reduce compliance. This research uses the probability sampling-proportional stratified random sampling method. The research sample was 100 taxable enterprises from the 10.697 population using the Slovin method. The results of the analysis show that tax morale, taxpayer awareness, tax justice, trust in government, tax authority power, tax convenience, and tax information have a positive effect on the compliance intention of taxable enterprises. The role of the theory of planned behaviour, and the slippery slope theory are also strengthened by the results of the analysis, which overall explain that the compliance behaviour of taxable enterprises is based on strong intentions, and the compliance intentions of taxable enterprises can increase if tax morale, taxpayer awareness, tax justice, trust in government, the power of tax authorities, tax convenience, and tax information increase